Examining Eating Attitudes and Behaviors in Collegiate Athletes, the Association Between Orthorexia Nervosa and Eating Disorders - Uriegas, Nancy A.; Winkelmann, Zachary K.; Pritchett, Kelly; Torres-McGehee, Toni M. (Frontiers in Nutrition, 2021)
Purpose: Orthorexia nervosa (Orthorexia) is the eating attitudes and behaviors associated with a fixation on healthy eating, while eating disorders (EDs) are clinically diagnosed psychiatric disorders associated with marked disturbances in eating that may cause impairment to psychosocial and physical health. The purpose of this study was to examine risk for Orthorexia and EDs in student-athletes across sex and sport type and determine the association between the two. Methods: Student- athletes (n=1090; age: 19.6±1.4 years; females=756; males=334) completed a survey including demographics, the ORTO-15 test (<40 and <35 thresholds), the Eating Attitudes Test-26 (EAT-26;>20 score), and additional questions about pathogenic behaviors to screen for EDs. Results: Using a <40 threshold for the ORTO-15, 67.9% were at risk for Orthorexia, a more restrictive threshold of <35 determined 17.7% prevalence across student-athletes with significant differences across sex (<40: χ21,1090=4.914, p=0.027; <35: χ21,1090=5.923, p=0.015). Overall, ED risk (EAT-26 and/or pathogenic behavior use) resulted in a 20.9% prevalence, with significant differences across sex (χ2=11.360, p<0.001) and sport type category (χ2 =10.312, p=0.035). Multiple logistic regressions indicated a significant association between EAT-26 subscales scores and Orthorexia, and between Orthorexia positivity, ORTO-15 scores, and risk for EDs. Conclusion: Risk for Orthorexia and ED is present in collegiate student-athletes. While healthy and balanced eating is important, obsessive healthy eating fixations may increase the risk for EDs in athletes. More education and awareness are warranted to minimize the risk for Orthorexia and EDs in student-athletes.